2002
DOI: 10.1179/cmq.2002.41.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Flotation of Sulfide Minerals with the use of a Cationic Collector

Abstract: In the flotation of Zn-Pb ores, sphalerite is floated following activation with copper sulfate. In this type of sulfide ore, pyrite is commonly treated as a gangue and poor selectivity between sphalerite and pyrite/quartz is often reported. But pyrite may also appear in association with gold and flotation of such auriferous sulfides is of great importance in many countries such as South Africa and Australia.In the cationic flotation of sulfide ores with dodecyl amine, sphalerite can be floated while depressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In most cases, the interaction between amine collectors and mineral surfaces is mainly due to the cation RNH + 3 or dimer RNH + 3 •RNH 2 of amines adsorbing on the negatively charged mineral surface via electrostatic attraction on the electric double layer of the mineral surface [10]. Laskowski [16] investigated the flotation behavior of dodecylamine on three single minerals, sphalerite, quartz and pyrite, and found that dodecylamine could be used to separate quartz from sphalerite in the high pH range (pH > 12.0), and also found that using lime and hydrogen peroxide as a combined inhibitor could inhibit pyrite effectively, thereby achieving the separation of sphalerite and pyrite. S.G. Malghan [10] investigated the mechanisms of sodium sulfide in the flotation of willemite and hemimorphite via the "sulfuration-amine" method.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the interaction between amine collectors and mineral surfaces is mainly due to the cation RNH + 3 or dimer RNH + 3 •RNH 2 of amines adsorbing on the negatively charged mineral surface via electrostatic attraction on the electric double layer of the mineral surface [10]. Laskowski [16] investigated the flotation behavior of dodecylamine on three single minerals, sphalerite, quartz and pyrite, and found that dodecylamine could be used to separate quartz from sphalerite in the high pH range (pH > 12.0), and also found that using lime and hydrogen peroxide as a combined inhibitor could inhibit pyrite effectively, thereby achieving the separation of sphalerite and pyrite. S.G. Malghan [10] investigated the mechanisms of sodium sulfide in the flotation of willemite and hemimorphite via the "sulfuration-amine" method.…”
Section: Introductionmentioning
confidence: 99%